Anthropogenic impact on the landscape of the Vishtynets Upland (Kaliningrad region, SE Baltic) in prehistory and Middle Ages: A multi-proxy palaeoenvironmental study. (20th January 2023) - Druzhinina, Olga; Stančikaitė, Miglė; Gedminienė, Laura; Vaikutienė, Giedrė; Lavrova, Nadezhda; Kublitskiy, Yuriy; Subetto, Dmitry
Abstract: The paper deals with an overview of early anthropogenic impact on the landscapes of the southeastern Baltic region and is based on the results of palaeolimnological and archaeological studies carried out on the Vishtynets Upland, Kaliningrad oblast, Russian Federation. The detailed study of available palynological (including microcharcoal), geochemical and archaeological data has revealed possible signs of anthropogenic impact on the landscape from the Early Mesolithic to the Middle Ages, while the results of lithological, geochronological and diatom analyses provided a basis for a better understanding of natural processes. Palynological data have shown that the first signs of human impact on landscapes date back to the Early Mesolithic (approximately from 10, 000 cal yr. BP), indicating the existence of local deforested areas. The presence of pollen from plantindicators of open habitats and pastures, as well as Pteridium and Corylus, combined with elevated Ba and Sr values as indicators of burning, suggests the deliberate burning of forests for the enhancement of hunting and mobility, as well as for the propagation of edible plants. The correlation of microcharcoal and pollen data has revealed several peaks of human activity in the Neolithic and showed that cultivation of Cerealia on the Vishtynets Upland began during this period (5120 - 4000 cal yr. BP). The first signs of metallurgy in the region emerged in the period 4500–3000 cal yr. BP (the late Neolithic – the Bronze Age) and are indicated by the simultaneous growth of V, Pb, Ni, Zn, As, Fe2 O3 and microcharcoal curves.